The role of the European Union in the fight against drugs. Special reference to its actions in Latin America - Anguita Osuna, José Enrique (REVISTA ELECTRONICA IBEROAMERICANA, 2023)
The fight against drugs has become a global problem that has to be addressed in coordination by all the actors involved, that is, international organizations, regions and States. The European Union has a vital role in this work, since, under the framework of international cooperation, it will have to continue developing its policy to combat illicit drug trafficking. The European Union has been fighting against drugs for many years, observing important achievements in the development of its action in this area. Although with the beginning of the community integration process the progress in the fight against drugs was more limited, thanks to the work, dedication and commitment shown in this field, it has managed to become a world leader in the fight against drug trafficking. and has been able to configure a series of instruments that make it possible to combat drugs effectively, highlighting the Agenda and the Action Plan, as well as the European Union Strategy on the fight against drugs. Furthermore, the European Union is promoting international cooperation with other regions in the field of drug trafficking eradication, giving priority to Latin America, with which, at different levels of action, it holds meetings and reaches significant agreements to continue fighting coordinated way against drugs.